2001
DOI: 10.2169/internalmedicine.40.1020
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Inappropriate Secretion of ADH (SIADH) Following Cisplatin Administration in a Pulmonary Adenocarcinoma Patient with a Malignant Pleural Effusion.

Abstract: Wereport a patient with pulmonary adenocarcinoma complicated by the syndromeof inappropriate secretion of antidiuretic hormone (SIADH) following systemic chemotherapy with cisplatin (CDDP) and vindesine (VDS). A 66-year-old womanwas diagnosed as having pulmonary adenocarcinoma with malignant pleural effusion following investigations for cough and dyspnea. After drainage of the effusion she received combination chemotherapy with CDDPand VDS. She developed SIADH 48 hours following chemotherapy. Interestingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Besides paraneoplastic, there is also one case of SIADH in advanced ONB induced by cisplatin (CDDP) [ 48 ]. A similar situation was also reported in some other cancer patients after CDDP administration [ 49 ].…”
Section: Syndrome Of Inappropriate Adh Secretionsupporting
confidence: 87%
“…Besides paraneoplastic, there is also one case of SIADH in advanced ONB induced by cisplatin (CDDP) [ 48 ]. A similar situation was also reported in some other cancer patients after CDDP administration [ 49 ].…”
Section: Syndrome Of Inappropriate Adh Secretionsupporting
confidence: 87%
“…However, accumulated effusion in this case was estimated to be only slight through the observation of chest X ray, suggesting that the elevation of the pressure should be limited. Because a previous report about SIADH assuming the involvement of elevated intra-thoracic cavity pressure as a cause of SIADH demonstrates the accumulation of a large amount of effusion which might be more than half of the thoracic cavity [8], the implication of pleural effusion for SIADH was assessed to be not significant in this case. Those findings suggested that SIADH in this case was not the secondary but, rather, the idiopathic type.…”
Section: Discussionmentioning
confidence: 95%
“…Hormone: Approximately 10% to 45% of SCLC and 1% of other lung cancer cases (squamous cell carcinoma 58 and adenocarcinoma 59,60 ) produce arginine vasopressin (ie, antidiuretic hormone [ADH]), but only 1% to 5% of patients with lung cancer have symptomatic syndromes of inappropriate ADH (SIADH). 11 Excess ADH activates vasopressin 2 receptors in renal tubules, resulting in increased aquaporins and impaired free water clearance.…”
Section: Syndrome Of Inappropriate Antidiureticmentioning
confidence: 99%